Method for comprehensively recycling waste lithium titanate negative electrode material

By calcining and pressurizing the waste lithium titanium titanate negative electrode material, lithium is selectively leaching and titanium-based adsorbent is solved, and high production costs are achieved in the existing technology, and high efficiency and low cost lithium recycling and titanium-based adsorbent preparation are achieved.

CN119710288AActive Publication Date: 2025-03-28GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411900337.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing methods of recycling lithium battery negative electrode materials cannot effectively increase the added value, and the production cost of titanium-based adsorbents is relatively high, making it difficult to meet the needs of low-cost preparation.

Method used

By calcining and pressurizing the waste lithium titanium titanate negative electrode material, lithium is selectively leaching, a high value-added titanium adsorbent precursor is prepared, and a titanium adsorbent is obtained through granulation.

Benefits of technology

Highly efficient selective leaching of lithium is achieved, and the leaching rate of lithium reaches more than 95%. The prepared titanium-based adsorbent has a high adsorption capacity and a porous structure, and is suitable for lithium extraction with alkaline, carbonate brine or lithium precipitated mother liquor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710288A_ABST
    Figure CN119710288A_ABST
Patent Text Reader

Abstract

The invention provides a method for recycling a waste lithium titanate negative electrode material, which comprises the following steps: S1, carrying out primary roasting on the recycled lithium titanate negative electrode material, mixing the obtained roasted material with a mixed solution containing an acidic salt and an auxiliary agent, carrying out pressurized reaction, and carrying out solid-liquid separation after the reaction is finished to obtain a lithium extraction solution and leaching residues; wherein the acidic salt is at least one of disulfate or ammonium salt; the auxiliary agent is at least one of barium chloride or calcium chloride; the pressure of the reaction is 0.3 to 0.6 MPa. According to the method, after the lithium titanate negative electrode material is subjected to pressurized selective leaching, a battery-grade lithium carbonate product can be prepared after the lithium extraction liquid is subjected to impurity removal, and the leaching residues can be used for preparing a titanium adsorbent precursor with a high additional value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrometallurgy and lithium extraction from salt lakes, and specifically relates to a method for comprehensive recycling of waste lithium titanate negative electrode materials. Background Art

[0002] With the promotion and application of lithium-ion batteries, many lithium-ion batteries have reached the scrap stage and need to be recycled. Some of the recycled lithium battery negative electrode materials are lithium titanate. The existing recycling method is to remove the organic solvent and then add lithium carbonate or titanium dioxide to roast and synthesize the lithium titanate negative electrode material, and its added value has not been improved.

[0003] At the same time, lithium recovery has become the main research direction of the new energy industry. Compared with battery lithium recovery and ore lithium extraction, salt lake lithium extraction has gradually become the mainstream direction of lithium extraction due to its high lithium extraction efficiency, relatively low cost, and environmental protection and greenness. The main processes for lithium extraction from salt lakes include precipitation, extraction, adsorption and electrodialysis. The more mature and widely used lithium extraction technology by adsorption is aluminum-based adsorption lithium extraction, but the application of aluminum-based adsorbents to extract lithium has limitations. It is more suitable for chloride-type brines with low sulfate and boron content. It is not suitable for alkaline brines, brines with high sulfate and boron content, or carbonate-type brines, because sulfate poisoning and boron poisoning are prone to occur, thereby affecting the stability of the adsorbent. In lithium extraction by adsorption, titanium-based adsorbents can be used for alkaline brines, brines with high sulfate or carbonate content, which makes up for some of the defects of aluminum-based adsorbents, so it has become the research focus of major lithium companies. However, the production cost of titanium-based adsorbents is high, and a low-cost preparation method is urgently needed. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for comprehensive recycling of waste lithium titanate negative electrode materials, which specifically treats the lithium titanate negative electrode materials to prepare a high-value-added titanium-based adsorbent precursor, which is then granulated into a titanium-based adsorbent that can be used for lithium extraction from salt lakes.

[0005] According to a first aspect of the present invention, a method for recycling waste lithium titanate negative electrode materials is proposed, comprising the following steps: S1: calcining the recovered lithium titanate negative electrode material, mixing the obtained calcined material with a mixed solution containing an acid salt and an additive for pressure reaction, and performing solid-liquid separation after the reaction to obtain a lithium extraction solution and leaching residue; Wherein, the acidic salt is at least one of a hydrogen sulfate salt or an ammonium salt; The auxiliary agent is at least one of barium chloride or calcium chloride; The reaction pressure is 0.3-0.6 MPa.

[0006] In some embodiments, the primary calcination temperature is 400-600° C., and the primary calcination time is 5-8 hours.

[0007] In some embodiments, the bisulfate salt is at least one of sodium bisulfate or potassium bisulfate; and / or, the ammonium salt is at least one of ammonium bisulfate or ammonium chloride.

[0008] The present invention selectively leaches the lithium titanate negative electrode material after calcination to remove organic matter by using acidic salts and additives. The chemical reaction formula can be as follows: 4NaHSO4+4BaCl2+ Li4Ti5O 12 =4NaCl+4BaSO4↓+4LiCl+5TiO2↓+2H2O; 2NH4HSO4+2CaCl2+ Li4Ti5O 12 =2NH3↑+2CaSO4↓+4LiCl+5TiO2↓+2H2O.

[0009] The lithium extraction liquid obtained after filtration can be used to prepare battery-grade lithium carbonate after impurity removal treatment. The leached residue contains titanium dioxide, which can be used as a raw material for preparing titanium-based adsorbents.

[0010] In some embodiments, the liquid-to-solid ratio of the calcined material to the mixed solution is (3-8) mL: 1 g; And / or, the concentration of the acidic salt in the mixed solution is 0.1-3 mol / L; And / or, the concentration of the auxiliary agent in the mixed solution is 0.1-0.8 mol / L.

[0011] In some embodiments, the reaction temperature is 200-300° C., and the reaction time is 5-8 h.

[0012] In some embodiments, the following steps are also included: S2: mixing the titanium source, the lithium source and the dispersant and ball milling them, and performing secondary calcination on the obtained ball milled material to obtain a titanium-based adsorbent precursor; S3: eluting the titanium-based adsorbent precursor and then granulating it to obtain a titanium-based adsorbent; Wherein, the titanium source is the leached residue described in step S1.

[0013] In some embodiments, in step S2, the lithium source is an organic lithium source; and / or the dispersant is an alcohol.

[0014] In some preferred embodiments, the organic lithium source is at least one of lithium oxalate or lithium acetate.

[0015] In some preferred embodiments, the alcohol is at least one of methanol, ethanol or ethylene glycol.

[0016] In some embodiments, in step S2, the rotation speed of the ball mill is 800~2000r / min; and / or, the mass ratio of the ball milling beads to the total mass of the titanium source and the lithium source in the ball mill is (4~8):1; and / or, the ball milling time is 3~8h.

[0017] In some embodiments, in step S2, the ball mill is first subjected to low-temperature drying treatment before secondary calcination, and the low-temperature drying temperature is 40-80° C. and the time is 6-10 hours.

[0018] In some embodiments, in step S2, the temperature of the secondary calcination is 800-1200° C., and the time of the secondary calcination is 6-12 hours.

[0019] In some embodiments, in step S2, the secondary calcination is performed under the protection of an inert gas.

[0020] In some embodiments, in step S3, the elution process is: mixing and stirring the titanium-based adsorbent precursor with an acid solution; the concentration of the acid solution is 0.15-0.4 mol / L, and the elution time is 3-8 hours.

[0021] In some preferred embodiments, the liquid-to-solid ratio of the acid solution to the titanium-based adsorbent precursor is (5-8) mL:1 g.

[0022] In some preferred embodiments, the acid solution is at least one of hydrochloric acid or sulfuric acid.

[0023] In some embodiments, in step S3, the granulation process is: mixing and stirring the eluted titanium-based adsorbent precursor with an organic solvent, a binder, a hydrophilic agent, and a porogen, and then extruding to obtain the titanium-based adsorbent.

[0024] In some preferred embodiments, the organic solvent is NMP (N-methylpyrrolidone); and / or the binder is PVDF (polyvinylidene fluoride) and PAN (polyacrylonitrile); and / or the hydrophilic agent is PEG (polyethylene glycol); and / or the porogen is at least one of sodium chloride or PVP (polyvinylpyrrolidone).

[0025] According to the second aspect of the present invention, a titanium-based adsorbent is provided, which is prepared by the preparation method described in the first aspect of the present invention, and the BET of the titanium-based adsorbent is 10~50m 2 / g, porosity is 30%-50%, particle size d=0.8~1.5mm; the adsorption capacity of the titanium-based adsorbent is above 3.5g / L.

[0026] According to the third aspect of the present invention, the use of the titanium-based adsorbent prepared by the method described in the first aspect of the present invention or the titanium-based adsorbent described in the second aspect in extracting lithium from carbonate brine or lithium precipitation mother liquor is proposed.

[0027] According to one embodiment of the present invention, there are at least the following beneficial effects: 1. The present invention innovatively utilizes the recycled negative electrode material lithium titanate as raw material, removes the organic matter on the negative electrode material, and then uses the method of high-pressure leaching with acidic salts and additives to achieve selective leaching of lithium. The leaching rate of lithium can reach more than 95%. After the lithium extraction solution is removed from the impurities, a battery-grade lithium carbonate product can be prepared; the titanium dioxide and dispersant after lithium extraction are prepared by adding lithium source mechanical ball milling-high temperature roasting coupling method to obtain a high-value-added titanium-based adsorbent precursor, and then eluted and granulated to become a lithium metatitanate adsorbent. Therefore, the present invention realizes the high-value recycling of lithium titanate negative electrodes of waste lithium-ion batteries by comprehensive recycling of lithium titanate negative electrode materials.

[0028] 2. The present invention uses acidic salts and additives to get rid of conventional acid leaching operations, reduce production costs, and make the process green and environmentally friendly. At the same time, the addition of additives can stabilize the adsorbent structure and enhance the hardness of the adsorbent, reducing the titanium dissolution loss during the adsorbent analysis process. On the other hand, the titanium adsorbent prepared by the present invention has a porous structure inside, providing more effective adsorption sites, and can be effectively used in the extraction of lithium from alkaline brine, carbonate brine or lithium precipitation mother liquor. The working adsorption capacity is above 3.5g / L, providing new ideas and methods for the research and development and application of titanium adsorbents in the direction of lithium extraction from salt lakes. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein: Figure 1 This is a flow chart of Embodiment 1 of the present invention; Figure 2 This is a SEM image of the titanium-based adsorbent precursor prepared in Example 1 of the present invention, magnified 10,000 times; Figure 3 This is a SEM image of the titanium-based adsorbent precursor prepared in Example 2 of the present invention, magnified 5000 times; Figure 4 This is a SEM image of the titanium-based adsorbent precursor prepared in Example 3 of the present invention, magnified 10,000 times; Figure 5 XRD comparison diagram of the titanium-based adsorbent precursor and lithium metatitanate Li2TiO3 prepared in Examples 1-3 of the present invention; Figure 6This is a SEM image of the internal structure of the titanium-based adsorbent after granulation in Example 1 of the present invention, magnified 11,000 times; Figure 7 This is a SEM image of the internal structure of the titanium-based adsorbent after granulation in Example 2 of the present invention, magnified 13,000 times. DETAILED DESCRIPTION

[0030] The concept and technical effects of the present invention will be clearly and completely described below in conjunction with embodiments to fully understand the purpose, features and effects of the present invention.

[0031] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods. Among them, lithium titanate, a negative electrode material for lithium batteries, is obtained by crushing and screening the negative electrode material for lithium batteries, wherein the content of lithium titanate is above 80%.

[0032] Example 1 This embodiment provides a method for comprehensive recycling of waste lithium titanate negative electrode materials, such as Figure 1 As shown, the specific steps include: S1: Take the recycled lithium battery negative electrode material lithium titanate, first roast it at 500℃ for 6h to remove its organic solvent, then transfer 500g of lithium titanate to the reactor, add sodium bisulfate solution and barium chloride auxiliary solution to react, the liquid-to-solid ratio in the reactor is 4 mL: 1 g, the concentration of sodium bisulfate in the reactor is 2 mol / L, and the concentration of barium chloride is 0.5 mol / L. Raise the temperature to 220℃ and react at a pressure of 0.3MPa for 5h. After the reaction is completed, filter to obtain lithium extraction solution and leaching residue, and the lithium leaching rate reaches 95.2%. The chemical reaction formula is as follows: 4NaHSO4+4BaCl2+ Li4Ti5O 12 =4NaCl+4BaSO4↓+4LiCl+5TiO2↓+2H2O; The leaching rate of lithium is calculated as follows: leaching rate = C*V / (m*ω), where C is the lithium concentration in the lithium extraction solution, in g / L; V is the volume of the lithium extraction solution, in L; m is the mass of lithium titanate, in g; ω is the mass fraction of lithium in lithium titanate, in %.

[0033] S2: Take 100g of the leached residue obtained in step S1, wash it with water, add 120g of lithium acetate and 600g of ethanol, mix them and perform mechanical ball milling. The mass of the ball milling beads is 900g, the ball milling speed is 1200r / min, and the ball milling is performed for 4h.

[0034] S3: The mixed material obtained in step S2 is transferred to an atmosphere furnace, first dried at 60°C for 8 hours, then heated to 900°C under nitrogen atmosphere protection and kept warm for 8 hours to obtain a titanium adsorbent precursor. The titanium adsorbent precursor particles are uniform and have no agglomeration. The SEM image is as follows: Figure 2 As shown, the XRD pattern is Figure 5 shown.

[0035] S4: The obtained titanium adsorbent precursor was added to 0.15 mol / L hydrochloric acid at a liquid-solid ratio of 5 mL:1g for elution, and then washed with water and dried. The obtained titanium adsorbent powder was granulated, and 18g PVDF and 1g PAN binder were added to 65g NMP, stirred in a water bath at 80°C for 1h, and then 5g PEG was added and stirred for 0.5h, followed by 20g sodium chloride and 100g titanium adsorbent powder and stirred for 1h. After stirring, it was extruded and granulated to obtain a titanium adsorbent, and its SEM image is shown as follows: Figure 6 shown.

[0036] The obtained titanium-based adsorbent was used to perform single-column adsorption verification on alkaline lithium precipitation mother liquor, and the results are shown in Table 1.

[0037] Table 1 Lithium adsorption data

[0038] The working adsorption capacity of titanium-based adsorbent is calculated by the following formula: Q e =V1(C0-C) / V2; Among them, Q e is the adsorption capacity, in g / L; V1 is the volume of the adsorption tail liquid, in L; C0 is the concentration of the adsorption original liquid, in g / L; C is the concentration of the adsorption tail liquid, in g / L; V2 is the volume of the adsorbent, in L; In this embodiment, the volume of the adsorbed tail liquid V1 is 0.3L, and the volume of the adsorbent V2 is 0.1L, so the working adsorption capacity of the titanium adsorbent is Q e =0.3L*(1.81g / L-0.61g / L) / 0.1L = 3.6g / L.

[0039] Example 2 This embodiment provides a method for comprehensive recycling of waste lithium titanate negative electrode materials, which specifically includes the following steps: S1: Take the recycled lithium battery negative electrode material lithium titanate, first roast it at 500℃ for 8h to remove its organic solvent, then transfer 500g of lithium titanate to the reactor, add sodium bisulfate solution and barium chloride auxiliary solution to react, the liquid-solid ratio in the reactor is 3mL:1g, the concentration of sodium bisulfate in the reactor is 2.8mol / L, and the concentration of barium chloride is 0.8mol / L. Raise the temperature to 230℃ and react at a pressure of 0.35MPa for 8h. After the reaction is completed, filter to obtain lithium extraction solution and leaching residue, and the lithium leaching rate reaches 95.6%. The chemical reaction formula is as follows: 4NaHSO4+4BaCl2+ Li4Ti5O 12 =4NaCl+4BaSO4↓+4LiCl+5TiO2↓+2H2O; S2: Take 100 g of the leached residue obtained in step S1, wash it with water, add 120 g of lithium acetate and 600 g of ethanol, mix them and perform mechanical ball milling. The mass of the ball milling beads is 950 g, the ball milling speed is 1100 r / min, and the ball milling is performed for 3 hours.

[0040] S3: The mixed material obtained in step S2 is transferred to an atmosphere furnace, first dried at 70°C for 6 hours, then heated to 850°C under nitrogen atmosphere protection and kept warm for 8 hours to obtain a titanium adsorbent precursor, the SEM image of which is shown in Figure 3 As shown, the XRD pattern is Figure 5 shown.

[0041] S4: The obtained titanium adsorbent precursor was added to 0.15 mol / L hydrochloric acid at a liquid-solid ratio of 5 mL: 1 g for elution, and then washed with water and dried. The obtained titanium adsorbent powder was granulated, and 19 g PVDF and 2 g PAN binder were added to 70 g NMP, stirred in a water bath at 80 ° C for 1 hour, and then 5 g PEG was added and stirred for 0.5 h, followed by adding 10 g PVP and 100 g titanium adsorbent powder and stirring for 1 hour. After stirring, it was extruded and granulated to obtain a titanium adsorbent, and its SEM image is shown as follows: Figure 7 shown.

[0042] The obtained titanium-based adsorbent was subjected to single-column adsorption verification on alkaline lithium precipitation mother liquor. The results are shown in Table 2. The working adsorption capacity was calculated to be 3.75 g / L.

[0043] Table 2 Lithium adsorption data

[0044] Example 3 This embodiment provides a method for comprehensive recycling of waste lithium titanate negative electrode materials, which specifically includes the following steps: S1: Take the recycled lithium battery negative electrode material lithium titanate, first roast it at 500℃ for 8h to remove its organic solvent, then transfer 500g of lithium titanate to the reactor, add sodium bisulfate solution and calcium chloride auxiliary solution to react, the liquid-solid ratio in the reactor is 4mL:1g, the concentration of sodium bisulfate in the reactor is 2.6mol / L, and the concentration of calcium chloride is 0.5mol / L. Raise the temperature to 230℃ and react at a pressure of 0.35MPa for 8h. After the reaction is completed, filter to obtain lithium extraction solution and leaching residue, and the lithium leaching rate is 95.3%. The chemical reaction formula is as follows: 4NaHSO4+4CaCl2+ Li4Ti5O 12 =4NaCl+4CaSO4↓+4LiCl+5TiO2↓+2H2O; S2: Take 100 g of the leached residue obtained in step S1, wash it with water, add 120 g of lithium acetate and 600 g of ethanol, mix them and perform mechanical ball milling. The mass of the ball milling beads is 950 g, the ball milling speed is 1100 r / min, and the ball milling is performed for 3 hours.

[0045] S3: The mixed material obtained in step S2 is transferred to an atmosphere furnace, first dried at 70°C for 6 hours, then heated to 850°C under nitrogen atmosphere protection and kept warm for 8 hours to obtain a titanium adsorbent precursor, the SEM image of which is shown in FIG. Figure 3 As shown, the XRD pattern is Figure 5 shown.

[0046] S4: Add the obtained titanium adsorbent precursor to 0.15 mol / L hydrochloric acid at a liquid-solid ratio of 5 mL: 1 g for elution, then wash with water and dry. Granulate the obtained titanium adsorbent powder, add 19 g PVDF and 2 g PAN binder to 70 g NMP, stir for 1 h in a water bath at 80 ° C, then add 5 g PEG and stir for 0.5 h, then add 10 g PVP and 100 g titanium adsorbent powder and stir for 1 h. After stirring, extrude and granulate it to obtain a titanium adsorbent.

[0047] The obtained titanium-based adsorbent was subjected to single-column adsorption verification on alkaline lithium precipitation mother liquor. The results are shown in Table 3. The working adsorption capacity was calculated to be 3.68 g / L.

[0048] Table 3 Lithium adsorption data

[0049] Comparative Example 1 This comparative example provides a method for comprehensive recycling of waste lithium titanate negative electrode materials, which specifically includes the following steps: S1: Take the recycled lithium battery negative electrode material lithium titanate, first roast it at 500℃ for 6h to remove its organic solvent, then transfer 500g of lithium titanate to the reactor, add sodium bisulfate solution and magnesium chloride solution to react, the liquid-solid ratio in the reactor is 4mL:1g, the concentration of sodium bisulfate in the reactor is 2mol / L, and the concentration of magnesium chloride is 0.5mol / L. Raise the temperature to 220℃ and react at a pressure of 0.3MPa for 5h. After the reaction is completed, filter to obtain lithium extraction solution and leaching residue, the lithium leaching rate is 92.1%, and the chemical reaction formula is as follows: 4NaHSO4+ Li4Ti5O 12 =2Na2SO4+2Li2SO4+5TiO2↓+2H2O; S2: Take 100g of the leached residue obtained in step S1, wash it with water, add 120g of lithium acetate and 600g of ethanol, mix them and perform mechanical ball milling. The mass of the ball milling beads is 900g, the ball milling speed is 1200r / min, and the ball milling is performed for 4h.

[0050] S3: The mixed material obtained in step S2 is transferred to an atmosphere furnace, first dried at 60° C. for 8 hours, then heated to 900° C. under nitrogen atmosphere protection, and kept warm for 8 hours to obtain a titanium-based adsorbent precursor.

[0051] S4: Add the obtained titanium adsorbent precursor to 0.15 mol / L hydrochloric acid at a liquid-solid ratio of 5 mL: 1 g for elution, then wash with water and dry. Granulate the obtained titanium adsorbent powder, add 18 g PVDF and 1 g PAN binder to 65 g NMP, stir for 1 h in a water bath at 80 ° C, then add 5 g PEG and stir for 0.5 h, then add 20 g sodium chloride and 100 g titanium adsorbent powder and stir for 1 h. After stirring, extrude and granulate it to obtain a titanium adsorbent.

[0052] The obtained titanium-based adsorbent was subjected to single-column adsorption verification on alkaline lithium precipitation mother liquor. The results are shown in Table 4. The working adsorption capacity was calculated to be 3.3 g / L.

[0053] Table 4 Lithium adsorption data

[0054] Comparative Example 2 This comparative example provides a method for comprehensive recycling of waste lithium titanate negative electrode materials, which specifically includes the following steps: S1: Take the recycled lithium battery negative electrode material lithium titanate, first roast it at 500℃ for 8h to remove its organic solvent, then transfer 500g of lithium titanate to the reactor, add sodium bisulfate solution and potassium chloride solution to react, the liquid-solid ratio in the reactor is 4mL:1g, the concentration of sodium bisulfate in the reactor is 2mol / L, and the concentration of potassium chloride is 0.5mol / L. Heat to 210℃ and react at a pressure of 0.3MPa for 7h. After the reaction, filter to obtain lithium extraction solution and leaching residue, and the lithium leaching rate is 89.6%.

[0055] S2: Take 100 g of the leached residue obtained in step S1, wash it with water, add 110 g of lithium acetate and 600 g of ethanol, mix them and perform mechanical ball milling. The mass of the ball milling beads is 850 g, the ball milling speed is 1200 r / min, and the ball milling is performed for 4 hours.

[0056] S3: The mixed material obtained in step S2 is transferred to an atmosphere furnace, first dried at 60° C. for 8 hours, then heated to 900° C. under nitrogen atmosphere protection, and kept warm for 8 hours to obtain a titanium-based adsorbent precursor.

[0057] S4: Add the obtained titanium adsorbent precursor to 0.15 mol / L hydrochloric acid at a liquid-solid ratio of 5 mL: 1 g for elution, then wash with water and dry. Granulate the obtained titanium adsorbent powder, add 18 g PVDF and 1 g PAN binder to 65 g NMP, stir for 1 h in a water bath at 80 ° C, then add 5 g PEG and stir for 0.5 h, then add 20 g sodium chloride and 100 g titanium adsorbent powder and stir for 1 h. After stirring, extrude and granulate it to obtain a titanium adsorbent.

[0058] The obtained titanium-based adsorbent was subjected to single-column adsorption verification on alkaline lithium precipitation mother liquor. The results are shown in Table 5. The working adsorption capacity was calculated to be 3.2 g / L.

[0059] Table 5 Lithium adsorption data

[0060] The titanium-based adsorbent obtained in Examples 1-3 was tested for BET, porosity and particle size, and the BET of the adsorbent was found to be 10-50 m 2 / g, porosity is 30%~50%, and particle size d=0.8~1.5mm. The particle size is tested according to GB / T 19077-2024 / ISO 13320:2020; BET is tested according to GB / T 19587-2017 / ISO 9277:2010, and the porosity is tested according to GB / T 42697-2023.

[0061] It can be seen from the above embodiments and comparative examples that the embodiments add barium chloride or calcium chloride as an auxiliary agent to selectively leach and extract lithium, and the leaching rate of lithium reaches more than 95%. The addition of other common chloride salts in the comparative example has no promoting effect on the lithium extraction process, and the leaching rate of lithium is less than 93%. In addition, the barium sulfate or calcium sulfate generated by the auxiliary agent added in the embodiments is an effective additive to the synthesis of the titanium-based adsorbent, which reduces the titanium dissolution loss during the adsorbent analysis process and improves the adsorption capacity of the titanium-based adsorbent, and its working adsorption capacity is above 3.5 g / L.

[0062] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for recycling waste lithium titanate negative electrode materials, characterized in that: The following steps are involved: S1: calcining the recovered lithium titanate negative electrode material, mixing the calcined material with a mixed solution containing an acid salt and an additive for pressure reaction, and performing solid-liquid separation after the reaction to obtain a lithium extraction solution and leaching residue; Wherein, the acidic salt is at least one of a hydrogen sulfate salt or an ammonium salt; The auxiliary agent is at least one of barium chloride or calcium chloride; The reaction pressure is 0.3~0.6MPa.

2. The method according to claim 1, characterized in that The liquid-to-solid ratio of the calcined material to the mixed liquid is (3-8) mL: 1 g; And / or, the concentration of the acidic salt in the mixed solution is 0.1-3 mol / L; And / or, the concentration of the auxiliary agent in the mixed solution is 0.1-0.8 mol / L.

3. The method according to claim 1, characterized in that The reaction temperature is 200-300° C., and the reaction time is 5-8 hours.

4. The method according to claim 1, characterized in that: The following steps are also included: S2: mixing the titanium source, the lithium source and the dispersant and ball milling them, and performing secondary calcination on the obtained ball milled material to obtain a titanium-based adsorbent precursor; S3: eluting the titanium-based adsorbent precursor and then granulating it to obtain a titanium-based adsorbent; Wherein, the titanium source is the leached residue described in step S1.

5. The method according to claim 4, characterized in that In step S2, the lithium source is an organic lithium source; and / or the dispersant is an alcohol.

6. The method according to claim 4, characterized in that In step S2, the temperature of the secondary calcination is 800-1200° C., and the time of the secondary calcination is 6-12 hours.

7. The method according to claim 4, characterized in that In step S3, the elution process is: mixing and stirring the titanium-based adsorbent precursor with an acid solution; the concentration of the acid solution is 0.15-0.4 mol / L, and the elution time is 3-8 hours.

8. The method according to claim 4, characterized in that In step S3, the granulation process is: mixing and stirring the eluted titanium-based adsorbent precursor with an organic solvent, a binder, a hydrophilic agent, and a porogen, and then extruding to obtain the titanium-based adsorbent.

9. A titanium-based adsorbent prepared by the method according to any one of claims 4 to 8, characterized in that: The BET of the titanium adsorbent is 10~50m 2 / g, porosity is 30%~50%, particle size d=0.8~1.5mm; the adsorption capacity of the titanium-based adsorbent is above 3.5g / L.

10. Use of the titanium-based adsorbent prepared by the method according to any one of claims 4 to 8 or the titanium-based adsorbent according to claim 9 in extracting lithium from carbonate brine or lithium precipitation mother liquor.

Citation Information

Patent Citations

  • Method for regenerating lithium titanate serving as anode material of waste lithium ion battery

    CN102390863A

  • Method for recovering lithium chloride and titanium dioxide from lithium titanate waste

    CN108550946A

  • Production of lithium titanate minute sintered particle

    JP2000281433A